Case report: FOXP1 syndrome caused by a de novo splicing variant (c.1652+5 G>A) of the FOXP1 gene - Chen, Min; Sun, Yixi; Qian, Yeqing; Chen, Na; Li, Hongge; Wang, Liya; Dong, Minyue (Frontiers in Genetics, 2022)
FOXP1 syndrome is a rare neurodevelopmental disorder characterized by global developmental delay, intellectual disability, and language delay, with or without autistic features. Several splicing variants have been reported for this condition, but most of them lack functional evidence, and the actual effects of sequence changes are still unknown. In this study, a de novo splicing variant (c.1652+5 G>A) of the FOXP1 gene was identified in a patient with global developmental delay, mild intellectual disability, speech delay, and autistic features. Assessed by TA-cloning, the variant promoted the skipping of exon 18 and a premature stop codon (p.Asn511*), resulting in a predicted truncated protein. This variant, that is lacking the forkhead-box DNA-binding domain and nuclear localization signal 2, may disrupt the protein function and thus cause FOXP1 syndrome related symptoms. Our study extends the phenotypic and allelic spectrum of FOXP1 syndrome.